Atraumatic suppurative mediastinitis and purulent pericarditis due to Eikenella corrodens. Issue 6 (June 1988) - Hardy, C C; Raza, S N; Isalska, B; Barber, P V
Abstract : Atraumatic suppurative mediastinitis is an uncommon infection. A case with an associated purulent pericarditis caused by Eikenella corrodens is reported.